Assessment of High Reliability Organizations Model in Farabi Eye Hospital, Tehran, Iran - Seyed Mohammad Hadi MOUSAVI; Mahmoud JABBARVAND BEHROUZ; Hojjat ZERATI; Hossein DARGAHI; Akram ASADOLLAHI; Seyed Ahmad MOUSAVI; Elham ASHRAFI; Abolfazl ALIYARI (Tehran University of Medical Sciences, 2017)
Background: A high-reliability organization (HRO) is a separate paradigm can indicate medical error reduction and patient safety improvement. Hospitals, as vital organizations in the health care system, can transform to HROs to achieve optimal performance and maximum safety in order to manage unpredicted events efficiently. Therefore, the aim of this research was to determine the knowledge of managers and staffs of Farabi Eye Hospital, Tehran, Iran about HROs model, and the extent of HROs establishment in this hospital in 2015- 2016. Methods: In this descriptive-analytical and cross-sectional study, data were collected through HROs questionnaire and checklist. Validity of questionnaire and checklist was confirmed by expert panel, and the questionnaire reliability by Alpha-Cronbach method with 0.85. The collected data were analyzed with Spearman's correlation coefficient and Mann-Whitney test using the SPSS software version 19. Results: Most of the respondents were familiar with HROs model to some extent and only 18.8% had a high level of knowledge in this regard. In addition, there was no significant correlation between the knowledge of staffs and managers with establishment of HROs model in Farabi eye hospital. Conclusion: Managers and staffs of Farabi Eye Hospital did not have a high knowledge level of the model of HROs and had little information about the functions and characteristics of these organizations. Therefore, we suggest HROs training courses and workshops should be established in this hospital to increase the knowledge of the managers and staffs for better establishment of HROs model.